Mirror The Fiction and Essays of Koda Aya - Sherif, Ann (University of Hawaii Press, 1999)
Ann Sherif discusses the life and work of Kòda in light of changes in critical horizons, readerly communities, and especially constructions of gender and the family in the latter half of the twentieth century. Excellent translations of some of Kòda's most provocative short works are included